Human capital of Akmola region: analysis and development prospects - Baigireyeva, Zh. (BUKETOV BUSINESS REVIEW, 2019)
The article discusses the prospects of human capital development of Akmola region-a leading branch of the agro-industrial complex in the formation of the food potential of the Republic of Kazakhstan. In this study, a detailed analysis of investments in the development of human capital of Akmola region of the Republic of Kazakhstan was carried out. Also in the article the analysis of areas of area was carried out, data of administrative centers and remoteness from the regional center are shown. The state programs in the field of human capital development of the country, such as the complex program «Nurly Zhol», «business Road map», etc. by types of investments in human capital of enterprises of Akmola region, as well as projects of publicprivate partnership in Akmola region, with which contracts have been signed, are presented in schematic form. The pace of raising funds in the sphere of medicine and health care of Akmola region and the health industry allows us to speak about the priority of the direction as one of the important directions. The leading institutions of Kazakhstan’s healthcare system are concentrated in Akmola region, medical clusters are actively developing, large-scale projects are being implemented. The article reflects the active and purposeful development of human capital in Akmola region. Strengthening the competitiveness of enterprises of Akmola region is possible in the set competent strategy, where you can get active labor returns through investments in social mobility, education, health care, reducing the loss of working time due to illness, increasing productivity. The leading factor of production is labor, which represents human capital in a market economy.